Occlusional Modifications Reversibly Alter Aquaporin 5 Expression and Localization in Rat Salivary Glands - Saito, Eri; Watari, Ippei; Mizumachi-Kubono, Mariko; Hsu-Hayashi, Sumire; Ono, Takashi (Frontiers in Physiology, 2020)
Background: Aquaporin 5 (AQP5) is a water channel forming protein that plays a key role in saliva secretion. A decrease in masticatory function associated with the molar extraction adversely affects the submandibular salivary gland (SMG) in rats and induces hypertrophic changes in the acinar cells and the expression of AQP5 in acinar cells or intercalated duct in the SMG. However, changes in AQP5 expression and localization in the SMG in association with occlusal modification have not been fully characterized. Methods: We examined the influence of the decline and recovery of masticatory function on expression and localization of AQP5 in the rat SMG using a protocol of insertion and removal of an incisor bite plate (IBP). Thirty 5-week-old male Wistar rats were randomly divided into the IBP group (n=12), recovery (REC) group (n=6), and the control (CON) group (n=12). Each rat in both the IBP and REC groups was fitted with the IBP on its maxillary incisors. Rats without the IBPs served as controls. All rats were fed powder diet and given water ad libitum. In the IBP and CON groups, rats were sacrificed after 14 (n=6) and 28 (n=6) days after the IBP attachment. In the REC group, the IBP was detached on 14th day and sacrificed on 28th day after the IBP attachment. AQP5 expression was quantified by RT-PCR and compared among the groups. Changes in the localization of AQP5 was tracked by immunohistochemical staining. Results: Attachment of IBP resulted in a decrease in the expression of AQP5 in IBP group. Changes in the localization of AQP5 was seen between 14 and 28 days in the IBP group, as indicated by immunohistochemical staining. In contrast, changes in the expression and localization of AQP5 were not observed in the REC group. Conclusion: Findings suggested that a loss of molar occlusion, due to the IBP attachment, altered AQP5 expression and localization in the rat SMG. However, Removal of the bite plate allowed the recovery of both AQP5 expression and its normal localization in the SMGs .